Website-Based Digitalization of the Expertise System (SiPAKAR) for Engineering Faculty Lecturers to Support SDGs 8 and 9: Digitalisasi Sistem Kepakaran (SiPAKAR) Dosen Fakultas Teknik Berbasis Website untuk Mendukung SDGs 8 dan 9 - Yeni Yulianti; Nur Riska; Ahmad Lubi; Shilmi Arifah; Ali Idrus; Sri Sundari (JOINCS (Journal of Informatics, Network, and Computer Science), 2025)
Study This aim develop system the expertise of the lecturers of the Faculty of Engineering, Universitas Negeri Jakarta (SiPAKAR) is web- based for make things easier search and mapping skill lecturer based on field knowledge, publications, and experience research. Development system use Research and Development (R&D) method with the Waterfall model and algorithm TextRank in keyword extraction​ publication. Research results show that system capable integrate data from Google Scholar, SISTER, and ORCID automatic. Data analysis using statistics descriptive for evaluate level validity and satisfaction TKT users in research This is at level 4-6 which is development system expertise in environment limited, including expert data processing lecturer from internal source. Validation test by experts produce level 'Very Adequate' eligibility (89%), and response users show satisfaction by 85%. SiPAKAR expected support transparency academic, collaboration research, and achievement of SDGs No. 8 (Decent Work and Growth) Economy) and No. 9 (Industry, Innovation, and Infrastructure). Although not yet perfect and still face obstacles, systems This is step strategic For strengthen the link between lecturers, expertise, and collaboration industry-academic. So that the impact more wide achieved, necessary supported by policies, incentives, technology and systematic monitoring.